Majas dan Citraan dalam Lirik Lagu Album Dunia Batas Karya payung Teduh dan Implementasinya Sebagai Bahan Ajar Sastra di SMK - Risnawati, Ellysa, Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum (2016)
EllysaRisnawati/A310 120 125.This study aimed to (1) describe the figurative contained in song lyric of Dunia Batas album by Payung Teduh, (2) describe the image contained in song lyric of Dunia Batas Album, (3) explain the context in song lyric of Dunia Batas Album, (4) describe the result of study in implementing the lesson. This study used descriptive qualitative method. The data of the study were utterance of Dunia Batas Album, and sentences. The data source in this study was song lyric of Dunia Batas Album by Payung Teduh. Technique of collecting the data were reference technique, listen, and record. This study used semiotic reading model that contained heuristic and hermeneutic model in analyzing the data. There were 4 results of this study (1) the most figurative that used in song lyric of Dunia Batas Album by Payung Teduh was personification, (2) the most image that used in song lyric Dunia Batas Album was movement image, (3) the content that could be understood based on analysing the figurative and image were missing, waiting, and restless, (4) this study could be implemented in literature learning at SMK in class XII especially in first semester. The criteria of choosing literature learning could be seen by several aspects such as language aspect, psychology aspect, and socio-cultural aspect. Keywords: Dunia Batas Album, image, song lyric ,figurative, literature learning.